Susceptibility of Biomphalaria amazonica and Biomphalaria occidentalis from Manso Dam, Mato Grosso, Brazil to infection with three strains of Schistosoma mansoni - Monica Ammon Fernandez; Silvana Carvalho Thiengo (Memorias do Instituto Oswaldo Cruz, 2006)
As well as malaria and yellow fever, schistosomiasis is one of the main endemic diseases associated to environments which suffered some impact related to the development of great economic projects, as for example the construction of hydroelectric power stations. Aiming to investigate the occurrence and distribution of freshwater snails of medical and veterinary importance in the area which suffered impact from the Manso hydroelectric power station a survey was performed during the period of 2002 to 2003 and revealed the occurrence of populations of Biomphalaria amazonica and Biomphalaria occidentalis. Studies on parasite-mollusc compatibility were undertaken using five B. amazonica colonies (Barão de Melgaço, Poconé, Santo Antônio do Leverger, and Chapada dos Guimarães, in the Manso and Casca rivers), and four B. occidentalis colonies (Cuiabá, Santo Antônio do Leverger, and Chapada dos Guimarães, in the Água Fria district and Casca river) were exposed to miracidia of Schistosoma mansoni. Of 257 snails of B. amazonica used, 17 became infected (infection index of 6.61%) and all specimens of B. occidentalis proved unsusceptible. According to the strains used, of the 158 snails exposed to BH miracidia, 6 became infected (3.79%); of the 44 exposed to SJ miracidia, 6 became infected (13.63%); and of the 55 snails of B. amazonica exposed to EC miracidia, 5 became infected (9.09%). These results point out the low possibility of introduction of schistosomiasis in those areas, but we believe it can not be discarded as due the presence of B. amazonica.